2020
DOI: 10.1038/s41598-020-73457-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of cold atmospheric plasma (CAP) with temozolomide in the treatment of U87MG glioblastoma cells

Abstract: Cold atmospheric plasma (CAP) technology, a relatively novel technique mainly investigated as a stand-alone cancer treatment method in vivo and in vitro, is being proposed for application in conjunction with chemotherapy. In this study, we explore whether CAP, an ionized gas produced in laboratory settings and that operates at near room temperature, can enhance Temozolomide (TMZ) cytotoxicity on a glioblastoma cell line (U87MG). Temozolomide is the first line of treatment for glioblastoma, one of the most aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 74 publications
2
48
0
Order By: Relevance
“…[29] Strikingly, we and others identified gas plasma treatment to have an immunological dimension [30,31] by inducing the immunogenic cancer cell death (ICD [32] ) in vitro [33,34] and in vivo. [35,36] Several reports have moreover suggested using gas plasma technology as anticancer agent against internal tumors [37] originating from, for instance, breast, [38][39][40] pancreatic, [41][42][43] colon, [44][45][46] liver, [47][48][49] central nervous, [50][51][52] ovarian, [53][54][55] and prostate [56][57][58] tissue. These and other studies also clearly demonstrated the importance of short-lived ROS/RNS in the induction of ICD.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Strikingly, we and others identified gas plasma treatment to have an immunological dimension [30,31] by inducing the immunogenic cancer cell death (ICD [32] ) in vitro [33,34] and in vivo. [35,36] Several reports have moreover suggested using gas plasma technology as anticancer agent against internal tumors [37] originating from, for instance, breast, [38][39][40] pancreatic, [41][42][43] colon, [44][45][46] liver, [47][48][49] central nervous, [50][51][52] ovarian, [53][54][55] and prostate [56][57][58] tissue. These and other studies also clearly demonstrated the importance of short-lived ROS/RNS in the induction of ICD.…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide is used as the gold standard for the treatment of high-grade GBM. Here, we reasoned that combining CAP with the commonly used chemotherapy drug temozolomide (TMZ) would enhance the treatment of GBM [12,13]. TMZ can extend the overall patient survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, indirect CAP treatment was effective for the treatment of CCA in vitro , selectively killing CCA cells over normal hepatocytes 25 . Research on CAP in combination with other therapies has shown some potential synergism with anti-neoplastic agents in melanoma cells 26 , drug loaded nanoparticles in breast cancer cells 27 , gemcitabine in murine pancreatic cancer cells 28 , and temozolomide in glioblastoma cells 29 .…”
Section: Introductionmentioning
confidence: 99%